Youth against hunger: service, activism and the mobilisation of young humanitarians in 1960s Britain. Issue 1 (2nd January 2016) - Bocking-Welch, Anna
Abstract: Youth have been a malleable resource in the fight against hunger, variously conceived as volunteers, political activists, global citizens and financial donors. This article uncovers competing (and sometimes complementary) visions for the participation of British youth in Youth Against Hunger, part of the United Nations Freedom from Hunger Campaign. In doing so, it makes two key contributions to the field. First, by uncovering the professionals and commentators who sought to involve adolescents in humanitarian activity, it accounts for the agency of a more diverse range of non-state participants and experts than are usually included in histories of humanitarianism. Second, in highlighting the pragmatic difficulties in aligning humanitarian and youth-work contexts, it illustrates how domestic concerns about British youth actively shaped the development of the humanitarian sector in this period.